Planning and Implementation of Islamic Religious Education in Shaping Elementary Students’ Religious Character - Rasidin; Neneng Hasanah; Kasful Anwar; Mahyuzar Rahman; Fransisko Chaniago; Amelia Febriana (MUMTAZ : Jurnal Pendidikan Agama Islam, 2025)
This research aims to examine how the planning and implementation of Islamic Religious Education (PAI) contributes to shaping the religious character of students at SDN 161/V Adi Purwa. The study was conducted using a qualitative method with a descriptive approach. Research data were obtained from the school principal, PAI teachers, and students. Data analysis was carried out through the stages of collection, reduction, presentation, and verification. The results indicate that the combination of structured planning and consistent implementation is effective in forming students' religious character. The students demonstrated a good understanding of religious values and the ability to apply them in daily life. Structured planning and effective implementation have proven successful in producing students who are faithful, pious, of noble character, and disciplined, in accordance with the objectives of Islamic Religious Education at SDN 161/V Adi Purwa.